2021
DOI: 10.1109/tfuzz.2020.2997467
|View full text |Cite
|
Sign up to set email alerts
|

Risk Models for Hazardous Material Transportation Subject to Weight Variation Considerations

Abstract: Reasonable risk models in hazardous material transportation are of practical significance, for safeguarding the lives and properties, protecting the natural environment, and facilitating the sustainable development. The existing risk models can be classified into summation risk model and maximum risk model, which result in over-reliance on overall risk or local risk. For overcoming these problems, we present two novel risk models considering different aggregation methods on local risks. The first model is supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Toumazis and Kwon (2013) presented a conditional VaR model that focuses on worst-case risk scenarios to avoid catastrophic local risks. Thus, Hu et al (2020a) developed an OWA risk model and an SVW risk model that consider weight variation in the models, with the aim of striking better results in jointly reducing global risk and local risk. Based on the aforementioned literature, we apply these two weight variation-based risk models to MDVRPs in hazmat transportation.…”
Section: Risk Measure For Hazmat Transportationmentioning
confidence: 99%
See 1 more Smart Citation
“…Toumazis and Kwon (2013) presented a conditional VaR model that focuses on worst-case risk scenarios to avoid catastrophic local risks. Thus, Hu et al (2020a) developed an OWA risk model and an SVW risk model that consider weight variation in the models, with the aim of striking better results in jointly reducing global risk and local risk. Based on the aforementioned literature, we apply these two weight variation-based risk models to MDVRPs in hazmat transportation.…”
Section: Risk Measure For Hazmat Transportationmentioning
confidence: 99%
“…However, this method overemphasises local risks and may lead to a route with a higher global risk. In order to overcome the disadvantage of the aforementioned models, Hu et al (2020a) proposed an ordered weighted averaging (OWA) risk model and an state variable weight (SVW) risk model for different weight information scenarios to achieve a better balance between global risk and local risk. Built on these two weight variation risk models this paper presents a study investigating into the more challenging, multi-depot vehicle routing problem (MDVRP).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, by examining the trend of changes in the amount of cost and emissions, it is observed that the percentage of changes in the rate of uncertainty in the cost objective function was much less than changes in emissions. Figure (3) shows the amount and percentage of changes in objective functions in exchange for changes in the rate of uncertainty. Due to the corruption of products in the proposed closed-loop supply chain network, there is a need for rapid transfer of products within a time limit from the supplier to the end customers.…”
Section: Analysis Of Sample Problemsmentioning
confidence: 99%
“…Specific stakeholders (e.g., environmentalists, the media) and the general public are highly sensitive to the dangers of transporting hazardous materials due to the involuntary nature and potential magnitude of these negative consequences. As a result, the government is usually in charge of regulating hazardous products transportation [3]. The importance of hazardous waste and products, as well as growing environmental concern, has necessitated the creation of a supply chain network for economically and environmentally hazardous products [4].…”
Section: Introductionmentioning
confidence: 99%
“…Hazmat transportation accidents may lead to leakage, explosion, poisoning, and other accidents, causing casualties, damage to property, and environmental damage. From 2013 to 2017, there were only 356 hazmat transportation accidents in China, but the accidents caused 855 deaths, 2980 injuries, and huge economic loss [2]. For example, on 16 January 2015, a collision accident of a gasoline tanker with three trucks on the Yinmachi Bridge of Rongwu Expressway caused 12 deaths and 11 million RMB economy loss; on 23 May 2017, a gas tanker exploded and caused 15 deaths and 3 injuries on the Zhangjiakou Shijiazhuang Expressway.…”
Section: Introductionmentioning
confidence: 99%